2016
DOI: 10.18632/oncotarget.13918
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation for rapid detection of pan-cancer microsatellite instability with MANTIS

Abstract: In current clinical practice, microsatellite instability (MSI) and mismatch repair deficiency detection is performed with MSI-PCR and immunohistochemistry. Recent research has produced several computational tools for MSI detection with next-generation sequencing (NGS) data; however a comprehensive analysis of computational methods has not yet been performed. In this study, we introduce a new MSI detection tool, MANTIS, and demonstrate its favorable performance compared to the previously published tools mSINGS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
239
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 255 publications
(244 citation statements)
references
References 33 publications
2
239
0
3
Order By: Relevance
“…Notably, this discordant endometrial tumor was also classified as MSS by MSI-PCR, and the consistency between these two assays raises the possibility that the tumor’s molecular signature may legitimately reflect a mutational process that is distinct from MSI (10,23). Regardless of this possibility, our findings reinforce the narrow validity of MSI-PCR only within colorectal cancers (15–17) and demonstrate that informed selection of larger numbers of informative markers by smMIP can recapitulate the pan-cancer performance of exome or genome-scale NGS diagnostic approaches for MSI (10,22,24,25). …”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Notably, this discordant endometrial tumor was also classified as MSS by MSI-PCR, and the consistency between these two assays raises the possibility that the tumor’s molecular signature may legitimately reflect a mutational process that is distinct from MSI (10,23). Regardless of this possibility, our findings reinforce the narrow validity of MSI-PCR only within colorectal cancers (15–17) and demonstrate that informed selection of larger numbers of informative markers by smMIP can recapitulate the pan-cancer performance of exome or genome-scale NGS diagnostic approaches for MSI (10,22,24,25). …”
Section: Discussionsupporting
confidence: 66%
“…By virtue of their ability to broadly interrogate the genome, these approaches offer substantial advantages over conventional methods in terms of diagnostic accuracy and applicability across cancer types (10,22,24,25). Nevertheless, determination of MSI by NGS currently requires large-scale targeted gene enrichment or exome sequencing data, which is material-limiting for many clinical specimens and results in a high cost of testing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSI analysis with MANTIS (version 1.0.3; commit #942061f) was performed as previously described 17 for all cases by using an average distance threshold of 0.4 to differentiate MSI-H from MSS tumors. Coordinates for 2,539 microsatellite loci within or near the exome—originally introduced by Salipante et al 15 and used by later studies 17 — were converted from hg19 to hg38 by using Lift- Over.…”
Section: Methodsmentioning
confidence: 99%
“…Examples of such software include mSINGS, 15 MSISensor, 16 and MANTIS. 17 A recent study by our group 17 demonstrated that MANTIS achieves high sensitivity (97%) and specificity (99%) across six cancer types—tested using samples with known MSI status by MSIPCR—and provides stable performance with varying numbers of microsatellite loci. Because of this, MANTIS is particularly well suited for application to a wider variety of cancer types.…”
Section: Introductionmentioning
confidence: 99%